Development of elasto-magnetic (EM) sensor for monitoring cable tension using an innovative ratio measurement method. (25th September 2018) - Ren, Liang; Xiu, Chengzhu; Li, Hongnan; Lu, Ye; Wang, Jiajian; Yao, Xuejia
Abstract: The magnetic permeability changes of ferromagnetic materials under elastic stress offer the potential to measure tension based on the inverse magnetostrictive effect. The elasto-magnetic (EM) sensor is the most promising technology for monitoring tension in steel structures. Nevertheless, difference in the device channel or variation of the external wire resistance results in an inaccurate induced voltage variation of the EM sensor in tension measurement. In this paper, the EM sensor for monitoring cable tension using an innovative ratio measurement method was presented. An inductor-resistor model of the excitation system and a transformer model of the sensor system were established to obtain the explicit relationship between the ratio result and the external tension. The experimental results show that the ratio of the integral value of the induced voltage to the excitation current variation is proportional to the external tension, a finding that is consistent with the theoretical derivation. In addition, the simulation analysis and experiment result demonstrate that the ratio measurement method improves sensor performance with the comparison of the traditional induced voltage method. Finally, the EM sensor was applied in the Zhengzhou Olympic Stadium of China. The monitoring results show that the proposed ratio measurement method could accurately measure cable tension.